Continuing professional development in HIV chronic disease management for primary care providers. (3rd August 2015) - Kang, Helen; Yip, Benita; Chau, William; Nóhpal De La Rosa, Adriana; Hall, David; Barrios, Rolando; Montaner, Julio; Guillemi, Silvia
Abstract: Primary care providers need continuing professional development (CPD) in order to improve their knowledge and confidence in the care of patients with chronic conditions. We developed an intensive modular CPD program in the chronic disease management of HIV for primary care providers. The program combines self-directed learning, interactive tutorials with experts, small group discussions, case studies, clinical training, one-on-one mentoring and individualized learning objectives. We trained 27 family physicians and 7 nurse practitioners between 2011 and 2013. The trainees reported high levels of satisfaction with the program. There was a 136.76% increase in the number of distinct HIV-positive patients receiving HIV-related medication refills that were prescribed by the trainees.